2021
DOI: 10.1101/2021.06.04.447114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-Picomolar Detection of SARS-CoV-2 RBD via Computationally-Optimized Peptide Beacons

Abstract: The novel coronavirus SARS-CoV-2 continues to pose a significant global health threat. Along with vaccines and targeted therapeutics, there is a critical need for rapid diagnostic solutions. In this work, we employ deep learning-based protein design to engineer molecular beacons that function as conformational switches for high sensitivity detection of the SARS-CoV-2 spike protein receptor binding domain (S-RBD). The beacons contain two peptides, together forming a heterodimer, and a binding ligand between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This specific approach of using trRosetta algorithm was intriguing to us because it was an available web-based platform and presented a scalable, efficient method for future researchers to conduct preliminary analysis into new mutations and variants that may not yet exist under natural conditions. Additionally, several studies have been reported on protein/peptide prediction of/against novel coronavirus SARS-COV-2 using trRosetta modeling suite [ 23 , 46 , 47 , 48 ]. Instead of time-consuming laboratory work to alter the genetic sequences of pathogens, large-scale computer generation of proteins could provide an avenue to narrow down mutations to study, discern patterns that can only be seen with large quantities of data and identify new therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…This specific approach of using trRosetta algorithm was intriguing to us because it was an available web-based platform and presented a scalable, efficient method for future researchers to conduct preliminary analysis into new mutations and variants that may not yet exist under natural conditions. Additionally, several studies have been reported on protein/peptide prediction of/against novel coronavirus SARS-COV-2 using trRosetta modeling suite [ 23 , 46 , 47 , 48 ]. Instead of time-consuming laboratory work to alter the genetic sequences of pathogens, large-scale computer generation of proteins could provide an avenue to narrow down mutations to study, discern patterns that can only be seen with large quantities of data and identify new therapeutics.…”
Section: Discussionmentioning
confidence: 99%